Premenstrual Hypersexuality and its Psychological Implications: A Case Series - Akanksha Sharma; Abdul Qadir Jilani; Aditi Bhatia; Christopher Peter (Journal of Psychosexual Health, 2026)
Objective: To describe the clinical characteristics, diagnostic evaluation and psychological management of premenstrual hypersexuality (PMH), a rare and under-recognised condition characterised by cyclical increases in sexual desire during the luteal phase of the menstrual cycle. Methods: We present a case series of three reproductive-age women who experienced recurrent increases in sexual desire, intrusive sexual thoughts and hypersexual behaviours occurring 7–10 days before menstruation, with spontaneous resolution following the onset of menses. All patients underwent comprehensive gynaecological, hormonal and psychiatric evaluations to exclude endocrine disorders and primary psychiatric conditions. Management consisted of individualised psychotherapy incorporating psychoeducation, cognitive restructuring, harm reduction strategies and supportive counselling. Outcomes were assessed over three consecutive menstrual cycles, including changes in the Female Sexual Distress Scale-Revised (FSDS-R). Results: All three patients demonstrated a consistent temporal association between symptom onset and the luteal phase, with significant psychological distress and interpersonal or functional impairment. Hormonal investigations and pelvic imaging were unremarkable, and no major psychiatric disorder was identified. Following psychotherapy, all patients reported reduced symptom-related distress and improved daily functioning while the cyclical pattern of increased sexual desire persisted. FSDS-R scores improved by approximately 10–15 points in each case, indicating clinically meaningful reductions in sexual distress. Conclusion: PMH is a rare but clinically significant presentation that may substantially affect psychological well-being and relationships. Recognition of its cyclical pattern is essential for accurate diagnosis. Individualised psychological interventions may effectively reduce associated distress, although further prospective studies are needed to establish prevalence, elucidate underlying mechanisms and develop evidence-based management strategies.